The Archaeology of Oman: A Preliminary Discussion of the Islamic Periods - Whitcomb, Donald S. (The Journal of Oman Studies, 1975)
In the winter of 1975 the Harvard Archaeological Survey returned to the Sultanate of Oman to continue its program of recording the archaeological remains of the prehistoric and historic periods within Oman. The primary focus was an intensive systematic survey in central Oman, from the drainage of the Wadi Bahla eastward into the Sharqiyah. In addition the survey undertook a more general reconnaisance of archaeological sites on the Batinah coast and in the southeastern region as far as Ras al-Hadd. The purpose of this study is to present the range of archaeological materials for the entire Islamic era resulting from this reconnaissance. For this archaeological outline, only a few sites have been selected as representative of particular historical periods and geographical situations in northern Oman.